Given:
Consider the given equation is
[tex](4x)^{-2}(4x)^3(4x)^9=(4x)^?[/tex]
To find:
The missing value in the given equation and complete the equation.
Solution:
We have,
[tex](4x)^{-2}(4x)^3(4x)^9=(4x)^?[/tex]
Taking LHS, we get
[tex]LHS=(4x)^{-2}(4x)^3(4x)^9[/tex]
[tex]LHS=(4x)^{-2+3+9}[/tex] [tex][\because a^ma^n=a^{m+n}][/tex]
[tex]LHS=(4x)^{10}[/tex]
and,
[tex]RHS=(4x)^?[/tex]
Let the missing value be k.
For each equation LHS=RHS.
[tex](4x)^{10}=(4x)^{k}[/tex]
[tex]10=k[/tex]
Therefore, the missing value is 10 and the complete equation is [tex](4x)^{-2}(4x)^3(4x)^9=(4x)^{10}[/tex].